Constructed Identity and Community Self-Expression to Perceive Human Security; Case Study of Klity Village, Kanchanaburi Province, Thailand - Assavarak, Passanan (Richtmann Publishing, 2012)
The lead released from a mine in Klity village killed many people, especially children. Moreover, it destroyed the ways of livesof the community and damaged the environment severely. The voices of the marginal Klity villagers have not been heard for over 10years. These voices of both physical and mental pain have finally led to the fight being heard and the faint voices have now beenamplified and heard by both the public and the ears of justice. The objective of this study is to discover how this overlooked communitywill be able to reconstruct their identity and create community self-expression in the public realm. Documentary research, participantobservation and interviews have been designed to collect data. The voice of Klity has never been heard until the media started torelease news about Klity. This communication is meant to allow the society to perceive facts and feelings. Simultaneously, thecommunity has had to struggle with structural power and mainstream cultures in order to receive recognition as humankind with humandignity as well as human security. The Klity case is the first environmental case in Thailand where the community has won a lawsuitagainst a powerful mine company and governmental organization, and this has raised public awareness about risk and socialconsciousness.